Basic principles of renewal of sportsmen with myofascial by a pain syndrome taking into account the psychological aspect of their rehabilitation - G.D. Kharchenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to examine and learn the fundamentals of the recovery of athletes with myofascial pain syndrome, taking into account the psychological aspect of their rehabilitation. Material: the data analyzed and summarized the scientific and methodological literature; sites on the internet. Results: the analysis of specialized literature on development features myofascial pain syndrome in athletes. Myofascial pain syndrome is widespread in sports practice. It is characterized by muscle spasms and trigger points, palpation of which there is a growing pain. The basic principles of the recovery of athletes with myofascial pain syndrome. The questions of the effectiveness of rehabilitation measures, taking into account the influence of psychological factors on the recovery of athletes. Conclusions: the presented strategy is comprehensive physical rehabilitation. Recommended keeping the basic principles of the recovery of athletes and the psychological aspect of their rehabilitation.